Sugar Policies: Opportunity for Change - Mitchell, Donald (World Bank, Washington, D.C., 2013)
Sugar is one of the most policy distorted of all commodities, and the European Union, Japan, and the United States are among the worst offenders. But internal changes in the E.U. and U.S. sugar and sweetener markets and international trade commitments make change unavoidable and provide the best opportunity for policy reform in several decades. The nature of reforms can have very different consequences for developing countries. If existing polices in the E.U. and the U.S. are adjusted to accommodate higher imports under international commitments, many low-cost producers, such as Brazil, will lose because they do not currently have large quotas and are not included among the preferential countries. The benefits of sugar policy reform are greatest under multilateral reform, and according to recent studies, the global welfare gains of removal of all trade protection are estimated to total as much as $4.7 billion a year. In countries with the highest protection (Indonesia, Japan, Eastern Europe, Western Europe, and the U.S.), net imports would increase by an estimated 15 million tons a year, which would create employment for nearly one million workers in developing countries. World sugar prices would increase by as much as 40 percent, while sugar prices in countries that heavily protect their markets would decline. Developing countries that have preferential access to the E.U. or U.S. sugar markets are likely to lose some of these preferences as sugar policies change. However, the value of preferential access is less than it appears because many of these producers have high production costs and would not produce at world market prices.